1968
DOI: 10.1029/wr004i001p00173
|View full text |Cite
|
Sign up to set email alerts
|

The use of soil maps in the delineation of flood plains

Abstract: Soil maps provide a tool for rapid, low‐cost delineation of river flood plains, based on the difference in morphology between soils frequently flooded and soils free of flooding. Very rare floods along the Mississippi River inundated over 99% of the soils that would be expected to flood but in addition flooded 7% of the terrace soils. Flooding predicted with soils information was compared with flooding predicted with an engineering study for small streams in a mature landscape in southwestern Wisconsin. For a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 4 publications
(2 reference statements)
0
13
0
Order By: Relevance
“…Likewise, in the 1960s, soil surveys were used in Fairfax County, Virginia to determine floodplain limits in support of county planning in areas where engineering or USGS floodplain studies had not been conducted (Coleman, 1963). Cain and Beatty (1968) investigated the use of soil maps to delineate the floodplains of streams in Wisconsin. They found that the soil‐based maps did a good job of showing areas that flooded, but their applicability to return frequency varied.…”
Section: Soil Maps As a Guide For Geologic Mapping—examples From The mentioning
confidence: 99%
“…Likewise, in the 1960s, soil surveys were used in Fairfax County, Virginia to determine floodplain limits in support of county planning in areas where engineering or USGS floodplain studies had not been conducted (Coleman, 1963). Cain and Beatty (1968) investigated the use of soil maps to delineate the floodplains of streams in Wisconsin. They found that the soil‐based maps did a good job of showing areas that flooded, but their applicability to return frequency varied.…”
Section: Soil Maps As a Guide For Geologic Mapping—examples From The mentioning
confidence: 99%
“…Indirect evidence of the frequency of individual prehistoric flood events can be obtained by a number of methods including botanical studies of floodplain vegetation [Sigafoos, 1964, Helley andLaMarche, 1973]; analysis of the degree of soil development on floodplain alluvium [Cain and Beatty, 1968], on flood bars [Bretz et al, 1956;Baker, 1973 Bretz, 1923b]. The anastamosing channel complex that trends northeast to southwest on the eastern side of the scablands is the Cheney Palouse tract referred to in the text.…”
Section: J Har/en Bretz and The Channeled Scablandmentioning
confidence: 99%
“…The extent of flooding during severe, infrequent storms can be approximated by comparing evidence from aerial photography and soils maps. The extent of alluvial soils has been shown to be a good indicator of areas inundated by large floods in several areas of the United States (Cain and Beatty 1968). Boundaries shown on preliminary soil survey maps for the north Scottsdale area are only approximate, and the availability of large-scale aerial photography (Table 1) permits more exact delineation.…”
Section: Flood Hazard Zone I--floodplains and Active Alluvial Fansmentioning
confidence: 99%